Immunomodulation of human intestinal T cells by the synthetic CD80 antagonist RhuDex® - Heninger, Anne-Kristin; Wentrup, Sabine; Saeedi, Mohammed al; Schiessling, Serin; Giese, Thomas; Wartha, Florian; Meuer, Stefan; Schröder-Braunstein, Jutta (Immunity, Inflammation and Disease, 2014)
Deregulated activation of mucosal lamina propria T cells plays a central role in the pathogenesis of intestinal inflammation. One of the means to attenuate T cell activation is by blocking the CD28/CD80 co-stimulatory pathway. Here we investigate RhuDex®, a small molecule that binds to human CD80, for its effects on the activation of lamina propria T cells employing a gut-culture model of inflammation.